Mobitz Type II Second-Degree Atrioventricular Block in a Pilot : To Pace or Not to Pace? - Stephanie Salim; Sunu Budhi Raharjo; Dony Yugo Hermanto; Dicky Armein Hanafy; Yoga Yuniadi; Stephanie Salim; Sunu Budhi Raharjo; Dony Yugo Hermanto; Dicky Armein Hanafy; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2020)
Background: Atrioventricular (AV) block is a threatening condition that caused sudden loss of consciousness and death, notably if happened to aircraft pilot will compromise the reliability of flight operations and safety. Cardiac arrhythmia is well known as one of the main disqualifier for loss of flying license, and discriminating between benign and potentially significant rhythm abnormalities remains a challenge. The present case describes the electrophysiological feature of a high-grade AV block in an aircraft pilot. Case illustration: A 60-year-old male worked as commercial aircraft pilot presented with asymptomatic high-grade AV block during inflight Holter monitoring. He had never experienced any remarkable symptoms nor history of near syncope, but had a history of percutaneous coronary intervention (PCI) with one stent at left circumflex (LCx) coronary artery. Electrophysiology (EP) study revealed AH interval of 105 ms, HV interval of 50 ms, AV node effective refractory period of 280 ms and Weckenbach point of 330 ms, suggesting a normal EP study. Stimulation with atrial pacing and ATP showed prolongation of AH interval without changes in HV interval, showing the presence of a supra-Hisian AV node dysfunction. The highly demanding physiological environment in aircraft elucidate the likelihood of vagotonic cause of his condition and pacemaker implantation was not warranted. Conclusion: Atrioventricular (AV) block is an AV conduction disorder that can manifests in various symptoms and severity. Electrophysiology study is considered as a modality to locate the site of block that allows the avoidance of unnecessary permanent pacing and the appropriate prophylactic pacing.